2019
DOI: 10.7150/ijbs.35630
|View full text |Cite
|
Sign up to set email alerts
|

The PACAP-derived peptide MPAPO facilitates corneal wound healing by promoting corneal epithelial cell proliferation and trigeminal ganglion cell axon regeneration

Abstract: It is well known that the cornea plays an important role in providing protection to the eye, but it is fragile and vulnerable. To clarify the biological effects and molecular mechanisms of the pituitary adenylate cyclase activating polypeptide (PACAP)-derived peptide MPAPO (named MPAPO) to promote corneal wound healing, we applied a mechanical method to establish a corneal injury model and analyzed the repair effects of MPAPO on corneal injury. MPAPO significantly promoted corneal wound repair in C57BL/6 mice.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…In addition to the inner and middle layers of the eye, we found strong immunoreactivity in the cornea part of the outermost, brous layer of the eye, where the outer epithelial and inner endothelial layers were positive for both the peptide and its receptor. PACAP treatment on the corneal surface has been shown to induce recovery of the epithelial cells and also of the sensory innervation (Fukiage et al 2007;Ma et al 2015;Wang et al 2019). PACAP KO mice present dry eye symptoms with corneal hyperkeratinization, also pointing at the importance of endogenous PACAP (Nakamachi et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the inner and middle layers of the eye, we found strong immunoreactivity in the cornea part of the outermost, brous layer of the eye, where the outer epithelial and inner endothelial layers were positive for both the peptide and its receptor. PACAP treatment on the corneal surface has been shown to induce recovery of the epithelial cells and also of the sensory innervation (Fukiage et al 2007;Ma et al 2015;Wang et al 2019). PACAP KO mice present dry eye symptoms with corneal hyperkeratinization, also pointing at the importance of endogenous PACAP (Nakamachi et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, PACAP eye drops prevent corneal keratinization in PACAP deficient mice (85). A PACAP-derived peptide has been shown to promote corneal wound healing (87,88). PACAP given in form of eye drops not only acts directly on the surface but also passes ocular barriers and is able to induce protective effects in the retina (163,164).…”
Section: Non-neuronal Parts Of the Visual System: Cornea And Retinal mentioning
confidence: 99%
“…PACAP binds to three G-protein coupled receptors, a higher affinity PACAP-specific receptor (PAC1), and two VIP/PACAP receptors (VPAC1 and VPAC2) with similar affinity for VIP and PACAP ( 34 ). PACAP has been found to be involved in neuroprotection, prevents apoptosis ( 35 , 36 ), promotes cell proliferation ( 37 ), neurogenesis and axonal regeneration in the central and peripheral nervous systems ( 38 , 39 ), and modulates immune and inflammatory responses ( 40 , 41 ). We previously reported that PACAP is secreted by sympathetic nerve endings projected into the BM, and can modulate HSPCs proliferation via PAC1 signaling ( 42 ).…”
Section: Introductionmentioning
confidence: 99%